A counterstory of resistance: The professional identity development of Latinx doctoral students in counseling programs. Issue 1 (6th December 2021) - Locke, Anna Flores
Abstract: This qualitative study applies a Latino Critical Race theoretical perspective to explore the role of White power and privilege on the professional identity developmental experiences of eight Latinx doctoral students in counseling programs. Three themes captured their counterstory: (a) being one of the few, (b) navigating professional identity, and (c) becoming a counselor educator. Implications aimed at retaining students of color and diversifying faculty are provided. Resumen: Este estudio cualitativo aplica la teórica crítica de la raza desde una perspectiva Latina para explorar el papel que ejercen el poder blanco y el privilegio en las experiencias de desarrollo de la identidad profesional de 8 estudiantes Latinx de doctorado en programas de consejería. Se captaron tres temas en su contrahistoria: (a) pertenecer a un grupo selecto, (b) navegar la identidad profesional y (c) convertirse en educador de consejeros. Se proporcionan implicaciones orientadas a la retención de estudiantes de color y la diversificación del profesorado.